Inclusive education in Portugal : teachers' professional development, working conditions, and instructional efficacy - Lopes, João Arménio Lamego (2022)
Inclusive education policies thin the boundaries of special and regular education as well as teachers’ roles and competencies. The present study, using data from TALIS 2018, aims to find out whether Portuguese teachers working in classes directed entirely or mainly to special education needs students (SENS) differ from teachers working in classes with few or no SENS in the following areas: (a) professional development needs in special education; (b) perceived barriers to professional development; and (c) teaching and work features related to SENS. The results show small but significant differences between teachers working and teachers not working entirely or mainly with SENS in professional development needs, perceived opportunities for professional development, and stress involved in modifying SENS lessons. No other significant differences were found. Still, the results show that both groups of teachers perceive significant professional development needs and barriers to professional development but are optimistic about the quality of professional development, job satisfaction, and self-efficacy in instruction. However, teachers of both groups are pessimistic about professional collaboration, a key element of inclusive education. Overall, it seems that some critical elements of inclusive education are still to be implemented in Portuguese schools. Keywords: inclusion; professional development; special education; SEN students; TALIS 20